Fruit Pest Control - Erb, Alan; Bauernfeind, Robert J.; Tisserat, Ned A. (My University, 1988)
This publication is for home gardeners who plant fruit trees, brambles, grapes, or strawberries. These gardeners would like to produce fruits without pests or disease.
C592_1998_11
Keywords: C592; Lawn and Garden; Insects; C